Two-photon energy distribution from the decay of the 2 1S0 state in He-like uranium - Banaś, Dariusz; Gumberidze, A.; Trotsenko, S.; Volotka, A. V.; Surzhykov, Andrey; Beyer, H. F.; Bosch, F.; Bräuning-Demian, A.; Fritzsche, S.; Hagmann, S.; Kozhuharov, C.; Kumar, A.; et al. (Physical review. A, Atomic, molecular, and optical physics, 2013)
We have performed a measurement of the spectral shape from the two-photon decay of the 1s2s1S0 state in He-like uranium. The two-photon emission followed the ionization of initially Li-like uranium ions in collisions with a N2 gas-jet target. The measured shape of the two-photon energy distribution shows good agreement with results of the relativistic calculations that take into account the electron-electron interaction rigorously up to the first order in quantum electrodynamic perturbation expansion. From the full width at half maximum of the measured two-photon energy distribution, we confirm the theoretically predicted modification of the shape due to the relativistic effects.
Gesehen am 01.12.2020
Im Titel ist die Ziffer "1" hochgestellt und die Ziffer "0" tiefgestellt